2021
DOI: 10.3390/ani11061761
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pelleted Diets in Commercially Farmed Decapods during Juvenile Stages: A Review

Abstract: The increasing market demand for decapods has led to a considerable interest in cultivating decapod species at a larger scale. Following the development of hatchery technologies, most research has focused on the development of formulated feeds for commercially farmed decapods once they enter the juvenile stages. The use of formulated feed for decapods at a commercial scale is still in the early stages. This is probably because of the unique feeding behavior that decapods possess: being robust, slow feeders and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 138 publications
(161 reference statements)
0
10
0
Order By: Relevance
“…From the proximate analysis, it is noticed that the lipid levels in diets are increased by increasing the level of fish oil, which subsequently resulted in a higher level of HUFA, particularly ARA, EPA, and DHA. Reportedly, Aaqillah-Amr et al [26,47] documented an increase in ARA, EPA, and DHA in the diets developed for S. olivacea broodstock fed with 120 g/kg lipids (ARA = 0:81 mg/g, EPA = 1:27 mg/g, and DHA = 1:20 mg/g) as compared to that fed with 60 g/kg lipids (ARA = 0:47 mg/g, EPA = 0:32 mg/g, and DHA = 0:26 mg/g). These findings indicated that the increase in HUFA contents increased the lipid level of the crustacean diets, which is important when it comes to signaling pathways and growth performance of decapod crustaceans [49].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…From the proximate analysis, it is noticed that the lipid levels in diets are increased by increasing the level of fish oil, which subsequently resulted in a higher level of HUFA, particularly ARA, EPA, and DHA. Reportedly, Aaqillah-Amr et al [26,47] documented an increase in ARA, EPA, and DHA in the diets developed for S. olivacea broodstock fed with 120 g/kg lipids (ARA = 0:81 mg/g, EPA = 1:27 mg/g, and DHA = 1:20 mg/g) as compared to that fed with 60 g/kg lipids (ARA = 0:47 mg/g, EPA = 0:32 mg/g, and DHA = 0:26 mg/g). These findings indicated that the increase in HUFA contents increased the lipid level of the crustacean diets, which is important when it comes to signaling pathways and growth performance of decapod crustaceans [49].…”
Section: Discussionmentioning
confidence: 95%
“…At the same time, ideal growth is achieved in a crustacean when micronutrients such as n-3 fatty acids are supplied at 8.6 mg/g for whiteleg shrimp [23], 12.7 mg/g for yellow mud crabs [24], and 30 mg/g for giant tiger prawn [25]. Lipids are among the most critical nutrient components required in crabs for energy expenditures, maturation, and growth [26,27]. The determination of lipid requirements in crabs is generally species-specific and varies according to different developmental stages.…”
Section: Introductionmentioning
confidence: 99%
“…Overfeeding can quickly overload the system and underfeeding or inadequate dietary formulations can result in nutrient deficiencies. In some cases, diets of low apparent digestibility and poor pellet integrity can compromise both growth and feed efficiency, as well negatively impact water quality, deteriorating the environmental conditions and animal health [19,20]. On the other hand, breeding has an important role to play to ensure that cultured shrimp supplied to super-intensive farms are well suited to the range of conditions likely to be experienced and that their production performance can be enhanced through an ongoing process of genetic improvement [21].…”
Section: Introductionmentioning
confidence: 99%
“…The highest FCR (1.51) was found in the control treatment ( Table 1 ). The FCR was inversely proportional to weight growth, so the lower the FCR, the higher the efficiency of the shrimp in utilizing feed for growth [ 37 ]. On the other hand, if the shrimp body is unstable, then the shrimp may experience a decrease in appetite and the feed provided is not converted into biomass.…”
Section: Resultsmentioning
confidence: 99%